IMAGE ANALYSIS OF PRODUCTS AND THE WORD OF MOUTH CUSTOMER SATISFACTION INCREASE IN CUSTOMER LOYALTY - Bagus Yunianto Wibowo; Misbakhul Arrezqi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The purpose of this research is to Investigate the effects of Product Image, Word of Mouth, Customer Satisfaction and Customer Loyalty. The study was conducted at custoers in PT.BRI Pandanaran Semarang, the sample size is about 119 customers. The data is processed using the Structural Equation Modeling (SEM) roomates assisted by the application program of Analysis of Moment Structure (AMOS) version 18.0. According to the analysis, it is concluded as the followings: product image has a positive effect on customer satisfaction; product image has a positive effect on customer loyalty; word of mouth has a positive effect on customer satisfaction; word of mouth has a positive effect on customers not loyalty; customer satisfaction has a effect on customer loyalty. Keyword: Product Image, Word of Mouth, Customers Satisfaction, Loyalty Customers